Romance and rights : the politics of interracial intimacy, 1945-1954 - Lubin, Alex (University Press of Mississippi, 2005)
Romance and Rights: The Politics of Interracial Intimacy, 1945-1954 studies the meaning of interracial romance, love, and sex in the ten years after World War II. How was interracial romance treated in popular culture by civil rights leaders, African American soldiers, and white segregationists? Previous studies focus on the period beginning in 1967 when the Supreme Court overturned the last state antimiscegenation law (Loving v. Virginia). Lubin's study, however, suggests that we cannot fully understand contemporary debates about "hybridity," or mixed-race identity, without first co